(untitled) (Research, Society and Development, 2020)
The alternative adopted in the breeding programs to decrease the effect of the genotype x environment interaction (G x E), is through the evaluation of the lineages in a network of experiments, these being conducted in several years and representative environments of the edaphoclimatic regions of cultivation. Therefore, the objective of this work was to evaluate the adaptability and productive stability of upland rice genotypes from the Minas Gerais, using the graphical tool for analysis of data, the GGE biplot. Grain yield data were used, derived from the evaluation of twenty rice lineages from the Cultivation Value and Use test of the Upland Rice Breeding Program at the Federal University of Lavras in partnership with Embrapa and Epamig. The tests were conducted in a complete block design, with three replications in the 2013/2014, 2014/2015 and 2015/2016 agricultural years. The experiments were conducted in a total of nine locations divided into the three agricultural years in the cities of Lambari, Lavras and Patos de Minas, all located in the state of Minas Gerais. It was concluded with this work that the lineages were almost entirely more adapted and stable than the commercial cultivars. The genotypes 10 and 13 were higher than the general average for productivity and showed high stability, being future candidates for launch as new cultivars.